The Importance of Digital Games in Learning - Nigmatova, Mavjuda (Центр Научных Публикаций (buxdu.uz), 2023)
This article analyzes educational digital games that can be an interesting way to study complex subjects that students usually do not prefer. In this exercise, several educational digital games are used as an educational tool that allows the learner to learn and understand complex subjects without undue stress.